Case report: Impact of mixed reality on anatomical understanding and surgical planning in a complex fourth ventricular tumor extending to the lamina quadrigemina - Colombo, Elisa; Bektas, Delal; Regli, Luca; van Doormaal, Tristan (Frontiers in Surgery, 2023)
Background and Importance: Tumors of the fourth ventricle count for 1-5% of all intracranial neoplastic lesions and present with different configurations and anatomical challenges.Microsurgery represents the primary therapeutic strategy for the majority of fourth ventricular tumors, and adequate anatomical understanding and visualization are paramount to surgical planning and success. Authors present the case of a young patient with a complex fourth ventricular tumor, whose surgery was successfully planned by means of a novel mixed reality (MxR) system.Case description: 31-year-old woman with a lesion extending from the fourth ventricle to the lamina quadrigemina and causing symptomatic hydrocephalus occlusus. Through the combined use of routine 2D images and an interactive 3D anatomical model, an interhemispheric transtentorial approach was used to remove 98% of the lesion with successful functional outcomes.Conclusions: The application of advanced 3D visualization with a novel MxR system to the surgical planning of a complex fourth ventricular lesion proved relevant to design the best surgical approach and trajectory, to better identify potential intraoperative challenges and rehearse the patient-specific anatomy. The present case report endorses the implementation of advanced 3D visualization in the routine perioperative practice.